1999
DOI: 10.1016/s0168-6445(99)00024-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial respiration of arsenic and selenium

Abstract: Oxyanions of arsenic and selenium can be used in microbial anaerobic respiration as terminal electron acceptors. The detection of arsenate and selenate respiring bacteria in numerous pristine and contaminated environments and their rapid appearance in enrichment culture suggest that they are widespread and metabolically active in nature. Although the bacterial species that have been isolated and characterized are still few in number, they are scattered throughout the bacterial domain and include Gram-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
207
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(214 citation statements)
references
References 58 publications
5
207
0
2
Order By: Relevance
“…strain PHS-1 (Kulp et al, 2008;Zargar et al, 2010), which was suggested to be conducted by a new arsenite oxidase clade, ArxA (Zargar et al, 2012), though no information is presently known on the this enzyme's functioning (van Lis et al, 2013). Through these processes, As speciation and bioavailability are altered, affecting its toxicity, environmental behavior and fate in the environment, and also its accumulation into food crops (such as rice) (Jia et al, 2014(Jia et al, , 2013Stolz and Oremland, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…strain PHS-1 (Kulp et al, 2008;Zargar et al, 2010), which was suggested to be conducted by a new arsenite oxidase clade, ArxA (Zargar et al, 2012), though no information is presently known on the this enzyme's functioning (van Lis et al, 2013). Through these processes, As speciation and bioavailability are altered, affecting its toxicity, environmental behavior and fate in the environment, and also its accumulation into food crops (such as rice) (Jia et al, 2014(Jia et al, , 2013Stolz and Oremland, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Gurunathan nanoparticles by Bacillus subtilis [19]. To date, about 16 diverse species of bacteria and Arechaea have been discovered to reduce selenium oxyanions to the red, amorphous or monoclinic allotropes of Se 0 [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Demethylation reactions by strict anaerobes (for example, Methanococcus) are improbable, on the one hand due to the (sub-)oxic conditions ( À 51 to þ 118 mV) at the wetland surface, and on the other hand because of the low aqueous Se concentrations (nM) 41,42 . More plausible are abiotic oxidation and demethylation reactions (for example, atmospheric instability and photo-oxidation in the transparent flow-through box), but comparing the reactions for Se, S and As is impeded by a lack of mechanistic and kinetic information, and further investigation is required.…”
Section: Resultsmentioning
confidence: 99%